Evaluation of Quercetin's Bioenhancing Effect on Oral Pharmacokinetics of Rosuvastatin in Wistar Rats Using RP-HPLC Method - Bhimanwar, Rachana S.; Kothapalli, Lata P.; Khawshi, Akshay (Cardiovascular & Hematological Agents in Medicinal Chemistry, 2024)
Background The absolute oral bioavailability of rosuvastatin (RST), a second-generation statin, is low i.e. 20% and only 10% is recovered as metabolite N-desmethy l rosuvistatin. Since it is a hydrophilic statin, RST relies on the organic anion transporting polypeptide-1B1 (OATP-1B1), as the key mechanism for active transport into hepatocytes. Quercetin (QUE) being a bio enhancer and inhibitor of OATP1B1 can augment the bioavailability and pharmacokinetics of RST. Objectives The present study includes the development of a simple and validated bioanalytical Reverse Phase High-Performance Liquid Chromatography (RP-HPLC) method for the estimation of RST and to study the effect of co-administration of QUE as a bio enhancer on its bioavailability. Methods An analytical column of Kromasil 100, C18 (250 mm × 4.6 mm, 5 μm), was used for chromatographic separationand acetonitrile (ACN): acetic acid buffer pH 3.0 adjusted with glacial acetic acid (55:45 Vol. %) as mobile phase with flow rate 1.0 ml/min monitored at 242 nm. The ACN: methanol (50:50 Vol. %) was employed as the final solvent for extraction. The developed method has been successfully applied in a study on the pharmacokinetics of the drug RST in rats after co-administration of QUE, which was carried out using non-compartmental analysis in order to estimate the blood concentration of the drug. Results The pharmacokinetics of RST was found to be altered significantly (highest concentration of RST in the blood (Cmax) = 67.3 ng/ml to 122.2 ng/ml) (p < 0.001), area under curve (AUC)0-t (p < 0.0001) and AUC0-inf (p = 0.0005) when co-administered with QUE at 120 min (tmax). Conclusion The results are in accordance with the fact that QUE increases plasma levels in rats through herb-drug interactions.
Keywords: quercetin